Tetrafluoroaryl Phosphonic Acid Functionalized Polyphosphazenes – Synthesis, Characterization, and Evaluation of Proton Conductivity. Issue 46 (28th September 2020) - Alter, Christian; Wiesemann, Markus; Neumann, Beate; Stammler, Hans‐Georg; Hoge, Berthold
Abstract : A convergent approach for the incorporation of tetrafluoroaryl phosphonate moieties into cyclic triphosphazenes and linear phosphazene resins is described. Our high yield procedure is based on the treatment of chlorinated poly‐ and cyclotriphosphazenes with p ‐HO(C6 F4 )P(O)(OR)2 (R = Me, Et) in the presence of potassium carbonate. Characterization of the modified cyclotriphosphazenes was accomplished by NMR and IR spectroscopy as well as by mass spectrometry. Similarly, a phosphazene resin decorated with phosphonic esters is characterized by NMR and IR spectra and GPC. Exchange of the ethyl group by a trimethylsilyl group in the novel phosphazene derivatives was effected by the reaction with trimethylsilyl bromide. The resulting silyl phosphonates were converted into the corresponding phosphonic acids by exposure to an excess of methanol. Proton conductivities of the novel phosphonic acid derivatives of poly‐ and cyclotriphosphazenes were studied by electrochemical impedance spectroscopy under anhydrous conditions. Abstract : A convergent approach for the incorporation of tetrafluoroaryl phosphonate moieties into cyclic and polymeric phosphazenes is described. Dealkylation of the phosphonates is affected by Me3 SiBr and subsequent methanolysis. Proton conductivities of the novel phosphonic acid derivatives of cyclotri‐ and polyphosphazenes were studied by electrochemical impedance spectroscopy under anhydrous conditions.